The Brass Verdict Book 2 - Connelly, Michael, 1956- (New York, New York : Little, Brown and Company, 2008)
When Hollywood lawyer Jerry Vincent is murdered, Mickey Haller inherits his biggest case yet: the defense of Walter Elliott, a prominent studio executive accused of murdering his wife and her lover. But as Haller prepares for the case that could launch him into the big time, he learns that Vincents killer may be coming for him next. Enter Harry Bosch. Determined to find Vincents killer, he is not opposed to using Haller as bait. But as danger mounts and the stakes rise, these two loners realize their only choice is to work together.
Keywords: Bosch, Harry (Fictitious character) -- Fiction; Lawyers -- California; Los Angeles; Fiction; Police -- California; Los Angeles; Fiction; Lawyers -- Crimes against; Fiction; Murder -- Investigation; Fiction; Los Angeles (Calif.) -- Fiction; Thriller